Game Based Learning in The Context of Physical Education in Indonesia - Rohmad Subagio; Yayat Ruhiat; Nani Maryani (Jurnal Penelitian Pendidikan IPA, 2026)
This study investigates the integration of Game-Based Learning (GBL) into physical education (PE) in Indonesia as an innovative pedagogical approach to enhance student engagement, motivation, and awareness of healthy lifestyles. GBL goes beyond standard teaching approaches by encouraging creativity, teamwork, and problem-solving abilities that are important for future difficulties. A quasi-experimental design was used with students from high schools who were split into an experimental group and a control group. The experimental group took part in physical education classes that included GBL techniques, whereas the control group received traditional teaching. Information was gathered through questionnaires about motivation and classroom observations. The quantitative data was evaluated using statistical comparison methods, while the observational results were utilized to enhance the understanding of student actions and involvement. The results showed that students in the GBL group exhibited greater motivation, engagement, and active involvement compared to those in the control group. Classroom observations showed increased collaboration, enthusiasm, and involvement in learning activities among students exposed to GBL. Furthermore, students in the experimental group reported greater awareness of the importance of physical activity and healthy lifestyle practices. The integration of GBL in PE positively influenced student motivation, engagement, and health-related awareness. Although its implementation requires careful planning, adequate resources, and institutional support, GBL offers a promising approach for improving learning experiences and promoting holistic student development in Indonesian physical education settings